BASICS OF GEOECOLOGICAL REGULATION OF LAND MANAGEMENT WORK (Scientific journal of the Fergana State University, 2024)
Today, the government of the Republic of Uzbekistan is actively working to expand protected areas, strengthen the material and technical base, and develop scientific potential. In the concept of environmental protection of the Republic of Uzbekistan until 2030, the expansion of categories of lands with environmental status is noted as one of the main strategic directions. The article analyzes the theoretical and practical aspects of the design and justification of protected natural areas during land management. The possibilities of expanding the natural reserve fund by analyzing the structure of land use and assessing anthropogenic load are also considered.